Policy in Community-Based Environmental Conservation and Protection: A Comparative Study Between Brazil and Indonesia - Diah Fitri Ekarini; Raldi H. S. Koestoer (Jurnal Wilayah dan Lingkungan, 2022)
Community-based environmental conservation and protection is one form of decentralization in the management of an area. Community-based initiatives are considered a sustainable collaborative alternative. The implementation of community-based initiatives can be found in various countries, such as the Voluntary Environmental Agents (VEA) in Amazon, Brazil and Social Forestry (SF) in Indonesia. This study aims to review the lessons learned from the CBC successful practice of VEA Program in Amazon, Brazil; determine whether these lessons can be adapted to enhance the positive impact of SF implementation in Indonesia, and; formulate relevant recommendations for SF implementation in Indonesia. A qualitative approach with descriptive-comparative method on references that are relevant to VEA and SF implementation was used in this study. There are several conditions that contribute to the successful VEA implementation: strengthening of local community initiatives, institutions, and capacities; formalization of community-based conservation schemes with supportive regulations; effective control system of the state; continuous support from external institutions, and; continuous and independent financing of activities. These conditions are relevant to be implemented in Indonesia. There is a fundamental difference between the implementation of VEA in Brazil and SF in Indonesia. Community-based initiatives in Brazil prioritized environmental sustainability to be able to “leverage” community’s economic and social sustainability in long term, while practices in Indonesia did not reflect this. This is illustrated by: lack of public awareness and concern for long-term environmental sustainability; negative impacts on the environment from SF implementation, and; vision of SF implementation which tends to be based on short-term targets.